Development of Natural Sciences Learning Media Based on Science Literacy on the Topic of Solar System in Elementary School - Miding, Maria Kristianti; Dinatha, Ngurah Mahendra; Lawe, Yosefina Uge; Kua, Maria Yuliana (research, training and philanthropy institution Natural Aceh, 2025)
The lack of learning media that enables students to learn makes it challenging to understand the learning material. This research aims to describe the design process of solar system multimedia products and determine the validation results of solar system multimedia products according to the results of expert reviews and individual trials. This development research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method. Data collection uses a questionnaire method. The research results show that the learning media developed has a very feasible category, with the results of student responses being very feasible with an overall average percentage of 95% and the results of teacher responses getting a percentage of 89.3% with a very feasible category. This demonstrates how well-suited the learning resources created for the solar system are for use as classroom instruction. According to the research, learning materials could be a solution for creating science learning materials that improve and ease students' comprehension, particularly regarding solar system content.